If you ain’t failin’, you ain’t tryin’ - Buckland, Amy; Ruest, Nick; Flemming, Declan; Hargrove, Scott (My University, 2011)
Amy Buckland facilitates this panel discussion about failing: projects that went nowhere, sideways, or just combusted and what was learned from the experience. These panelists, experts on the topic, will convince us that failing can be fun and worthwhile.
(video)
Keywords: fail; drupal; digital collections; Library and Information Science; Library and Information Science